(untitled) (Research, Society and Development, 2018)
This study has the purpose of demonstrating the importance of the management of solid waste from construction, exposing the importance of the Solid Waste Management Plan and presenting the benefits and advantages of the Solid Waste Management Plan for the work, the construction industry generates tons of solid waste every year, where the vast majority of these wastes are disposed of inappropriately and without concern for the environment. In addition to the exacerbated and exorbitant production of waste, there is still an increase in the cost of materials due to the lack of management of the waste, which results in waste and, consequently, the dumping and accumulation of solid waste in nature. The research was carried out by carrying out the bibliographic review in authors who have already discussed and researched the subject. It was concluded at the end of writing that the implementation of the Civil Construction Waste Management Plan is perfectly viable for civil construction and the benefits go from a reduction of 50% to 96% in solid waste generation per month in the works construction. This represents gains for the company and for the environment.